Irradiation resistance of preceramic paper‐derived SiCf/SiC laminated composites - Li, Ke; Kashkarov, Egor; Ma, Hailiang; Fan, Ping; Zhang, Qiaoli; Zhang, Peng; Cao, Xingzhong; Zhang, Jilong; Wu, Zhaohui; Lider, Andrey; Travitzky, Nahum; Yuan, Daqing (Journal of Materials Science, 2022)
Influence of the ion irradiation at elevated temperatures on the novel preceramic paper-derived SiCf/SiC laminated composites fabricated by spark plasma sintering was investigated. The composites were subjected to high-dose simultaneous irradiation of silicon (Si) ions at 400 °C. Irradiation induces amorphization of the damaged area up to 30 dpa, and then recrystallization of amorphous regions with increasing dose occur. No evidence of cavities was found in SiCf/SiC composites irradiated by silicon ions up to 100 dpa. The irradiated composites pre-injected with 5000 appm He displays low swelling ( 0.3%). The irradiation with Si ions may suppress the cavity nucleation and they growth in SiC layers.
CRIS-Team Scopus Importer:2022-06-10